Survival Rates for Northern Bobwhites on Two Areas with Different Levels of Harvest - Willie J. Suchy; Ronald J. Munkel (National Quail Symposium Proceedings, 2017)
We estimated survival rates for radio-marked northern bobwhites ( Colinus virginianus) in south-central Iowa from I 984 to I 988. Survival rates and survival functions were calculated for 2 areas that received different and varied amounts of hunting pressure. Survival from fall-spring averaged 17.1 % ± 6.9% on the Brown's Slough study area (BSSA) and 20.1 % ± 5.7% on the Millerton study area (MSA). Although these estimates were not different (P = 0.898), the survival functions did differ between the 2 areas (x2 = 25.82, P<0.001). Mortality due to hunting averaged 27.7% ± 8.2% on the BSSA during the fall-spring period and 12.3% ± 4.9% on the MSA. Predators accounted for 52% of fall-spring mortality on the BSSA and 79% of the mortality on the MSA. The BSSA had much lower rates of predation the 2 months following the hunting season. Survival rates during both the spring-fall period and annually did not differ between the 2 areas (P = 0.395 and P = 0.979). Hunting did not appear to be a limiting factor for quail numbers on these areas during the study.